Severe lower urinary tract symptoms due to anteriorly located midline prostatic cyst arising from the bladder neck in a young male: case report - Gürağaç, Ali; Demirer, Zafer; Alp, Bilal Fırat; Aydur, Emin (São Paulo Medical Journal, 2016)
CONTEXT: Prostatic cysts are uncommon. These cysts are usually asymptomatic and are diagnosed incidentally during ultrasonographic examination. On rare occasions, they may cause drastic symptoms. CASE REPORT: We report on a case of severely symptomatic anteriorly located prostatic cyst arising from the bladder neck in a 30-year-old man presenting with lower urinary tract symptoms, without clinical evidence of benign prostatic hyperplasia. Transrectal ultrasonography (TRUS), computed tomography (CT) and cystourethroscopy demonstrated a projecting prostatic cyst that occupied the bladder neck at the precise twelve o’clock position. It was acting as a ball-valve, such that it obstructed the bladder outlet. Transurethral unroofing of the cyst was performed and the patient’s obstructive symptoms were successfully resolved. Histopathological examination indicated a retention cyst. CONCLUSIONS: It should be borne in mind that midline prostate cysts can be a reason for bladder outlet obstruction in a young male. Such patients may have tremendous improvement in symptoms through transurethral unroofing of the cyst wall